Youth attitudes towards the economic and social impacts of inbound tourism in the Kingdom of Saudi Arabia - Norah Basheer Alotaibi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The study aims to identify youth attitudes towards the economic and social impacts of inbound tourism in the Kingdom of Saudi Arabia, by identifying the economic and social impacts. The study relied in its theoretical framework on the theory of trends. The study also benefited from previous studies and theoretical literature specialized in the field of tourism and social sciences. The study is considered one of the descriptive studies based on collecting and analyzing field data, which depends on the quantitative approach through the use of the social survey method through the random sample. In order to achieve the objectives of the study, a questionnaire was designed to determine the youth’s attitudes towards the economic and social impacts of incoming tourism in the Riyadh region, as it is the capital and the most densely populated area. The study reached a set of results, the most important of which are: Tourism raised the level of individuals ’income. The human being to enjoy free time, interest in archaeological sites is a factor that attracts tourists, and one of the most important proposals that the study reached for the development of inbound tourism is to exploit villages in which there are natural elements to attract tourists, employ trained tourist guides, encourage businessmen to support domestic tourism, open institutes and specialties in the tourism field .